The Evidence of Obstruction: A Hermeneutic Approach to Fundamentalist Thought - Taher, Murtada Jaleel (Thi Qar Arts Journal, 2022)
The research stems from the problem of the reliability of understanding offered by religious texts in whether this problem is related to the nature of the discourse and its context or the nature of the transmission methods and the security gaps that follow for its purpose and purposes. This problematic is in the framework of establishing a presumptive understanding after acknowledging the inefficiency of the guarantor data, and then changing the bridging between the fundamentalist given and the modern interpretive understanding without dissolving the specificity of the approach